A review of recharge and clogging in sandstone aquifer. (September 2020) - Song, Wei; Liu, Xiaoxiu; Zheng, Tuanfeng; Yang, Jiaming
Highlights: We review recharge and clogging development in groundwater heat pump systems. Clogging mechanisms, controlling factors, and recovery measures are summarized. Future research should focus on the visualization of physical clogging mechanisms. Abstract: Groundwater heat pump (GWHP) systems are widely used to exploit shallow geothermal energy because of their stable temperature, high efficiency, and excellent heat transfer capabilities. However, the recirculation problem caused by clogging is a key limitation to the sustainable operation of GWHP systems. Because of weak diagenesis, multiple suspended particles exist within the rock structure, and the permeability of a sandstone aquifer is lower than that of strongly fractured, karstisfied, or deeply weathered aquifer, which complicates the recharge procedure and even reduces the operating lifetime of the system. During the recharge process, water temperature, seepage velocity, and aquifer environmental characteristics affect the formation mechanism and development of clogging, which exists in physical, chemical, and biological forms, making it difficult to diagnose the causes of clogging. In this review, the factors affecting clogging and corresponding preventive and recovery measures are summarized. We suggest that future research should analyze the trajectories and sedimentary characteristics of suspended particles after entering the aquifer on a microscopic scale. Moreover, visualizing the clogging mechanism could provide a powerful basis for manual intervention. We also propose establishing real-time monitoring using a risk intelligent monitoring system for the sandstone thermal extraction and reinjection process based on data and emerging risks. This would enable reasonable adjustments to be taken before clogging occurs. This review suggests beneficial directions for future research and clogging control.